Carborane induced excimer emission of severely twisted Bis-o-carboranyl chrysene - Heeney,MJ; Stavrinou,P; Anthony,S; Colin,W; Beaves,P; White,A; Dyson,M; Little,M; Cheetham,N; Marsh,A (Angewandte Chemie, 2018)
The synthesis of a highly twisted chrysene derivative incorporating two electron deficient ocarboranyl groups is reported. The molecule exhibits a complex, excitationdependent photoluminescence, including aggregationinduced emission (AIE) with good quantum efficiency and an exceptionally long singlet excited state lifetime. Through a combination of detailed optical studies and theoretical calculations, the excited state species are identified, including an unusual excimer induced by the presence of ocarborane. This is the first time that ocarborane has been shown to induce excimer formation ab initio, as well as the first observation of excimer emission by a chrysenebased small molecule in solution. Bisocarboranyl chrysene is thus an initial member of a new family of ocarboranyl phenacenes exhibiting a novel architecture for highlyefficient multiluminescent fluorophores.